THE UNIVERSITY: DISSEMINATION AND SCIENTIFIC PUBLICATION - Rodríguez-Chávez, Elio Iván (2019)
Ricardo Palma University, as a leading institution of higher education, is strongly committed to promoting scientific dissemination and the publication of quality scientific journals. In the era of knowledge, and instant knowledge, having scientific journals indexed and available online brings enormous benefits, both for the university community and for the scientific community in general.